QUALITY OF LIFE OF PATIENTS WITH CHRONIC HEART FAILURE WITH PRESERVED HEART BLOOD SHOT HUSSITE AND BENDOPNEA SYMPTOM - Abdullayeva K. H.; Uzbekova N. R.; Bektasheva G. M. (Web of Journals Publishing, 2024)
To study the compartments of fat depots and some cardiometabolic markers in patients with chronic heart failure with preserved ejection fraction (CHF), prediabetes and abdominal obesity. In the studied sample, the values of body weight, glomerular filtration rate and concentration of NT-proBNP in blood plasma were higher in men compared with these indicators in women. The level of NT-proBNP in men with grade 3 obesity turned out to be minimal, only slightly exceeding the diagnostic limit. The highest rates of HFRS were recorded in women with obesity of the 2nd and 3rd degrees, which emphasizes their pro-inflammatory status. Visceral epicardial and pre-abdominal fat compartments did not differ significantly in both sexes.
Keywords: chronic heart failure with preserved ejection fraction, prediabetes, obesity, NT-proBNP, C-reactive protein, epicardial fat, premesenteric fat, subcutaneous fat, men, women.